Implementación de un plan de mantenimiento para el área de producción de la empresa industrias metálicas "Muñoz" mediante el software Sis Mac versión estudiantil. - Muñoz Contreras, Shirley Paola (2020)
The purpose of this work is to present the implementation of the maintenance plan using SisMAC software for the production area of the company Industrias Metálicas Muñoz. Through the inventory, critical analysis and visit to the company located in the Cayambe canton, it will be determined what is necessary to improve the maintenance plans. Review quarterly corrective maintenance, with the coding methodology, sense of technical states of the machines that offer the SisMAC program and the criticism of each of them through a study matrix, the most appropriate preventive maintenance action is determined according to each operating context, with the most critical equipment having the greatest number of tasks and those whose criticism is low have fewer actions. The information obtained through the visit to the company, the inventory, the technical data sheets and the other maintenance information is managed by the software, resulting in an immediate response to any type of failure mode that may occur in the assets of the company, guaranteeing the scope of their useful life. With the project, the management of the equipment was improved and, at the same time, its availability has increased, which can provide notable reliability in their operation. Key words: SisMAC, active, criticality, reliability, maintenance.